Physics in Minerva’s Academy - Ducheyne, Steffen (Brill, 2025)
This monograph explains how, in the aftermath of the battle over René Descartes’ philosophy, Newton’s natural philosophy found fertile ground at the University of Leiden. Newton’s natural philosophical views and methods, along with their underlying distinctions, seamlessly aligned with the University of Leiden’s institutional-religious policy, which urged professors and students to separate theology from philosophy. Additionally, these views supported the natural philosophical agendas of Herman Boerhaave, Willem Jacob's Gravesande, and Petrus van Musschenbroek. Newton’s natural philosophical program was especially useful in the three Leiden professors' project of reforming existing disciplines and providing them with epistemic legitimacy.